Non-Observance of Maxims in Ask.fm Social Q&A Website - Fina Kamilah (Passage, 2017)
This paper entitled “Non-Observance of Maxims in Ask.fm Social QA Website” investigates the types of maxims and non-observance of maxims which are broken on purpose by Ask.fm users. It also examines some possible reasons for breaking the maxims. By employing Grice’s (1975) cooperative principle, this qualitative study examines one hundred interactions of Ask.fm users. The findings reveal that maxim of quantity, relation and manner are types of maxims which are not obeyed by the users. In addition, the types of non-observance of maxims identified in this study are flouting and opting out. Finally, reasons for breaking maxims are due to the intention to create jokes, to please others and to avoid cyberbullying. Overall, the findings suggest that by performing non-observance intentionally, it does not necessarily lead to communication breakdown. In fact, it made the conversation in Ask.fm more interesting, relax, and lively.Keywords: Grice’s Cooperative Principle, Non-observance of maxims, social media, website, Ask.fm